Effect on weight after Albendazole therapy among the primary school children in a slum of Kolkata - Bhattacharyya, Madhumita; Sinha, Rabindra Nath; Sarkar, Asim; Mallick, Ashok Kumar; Panda, Asit Kumar (National Journal of Community Medicine, 2018)
Background: One of the major public health problems in tropical countries including India is soil transmitted helminthiasis (STH) which not only causes morbidity of children but also affects the growth and nutritional status of children. World Health Organisation recommended Albendazole as safe and cost effective medicine for STH. Objective: This study was conducted to assess the effect of Albendazole on the weight gain and worm related morbidity among the children of schools situated in an urban slum area of Kolkata. Methods: This was a double- blind, placebo controlled school based interventional study. Six twenty six school children of 6 to 10 years old were randomly selected to receive either Albendazole or placebo. One group received two doses of Albendazole (400mg) 3months apart and another group received placebo. Results: Mean weight gain of children was significantly higher in study group (Albendazole group) than the control groups after 6 months .The study group also experienced less episode of diarrhoea ,worm expulsion and gastrointestinal problems than control group. There was no adverse effect reported. Conclusion: Periodic deworming is effective and safe for school children and it has also effect on weight gain and reduction of morbidity among the school children.